2007
DOI: 10.1074/jbc.m611555200
|View full text |Cite
|
Sign up to set email alerts
|

Closed-state Cross-linking of Adjacent β1 Subunits in α1β1 GABAa Receptors via Introduced 6′ Cysteines

Abstract: The pore structural changes associated with Cys-loop receptor gating are currently the subject of considerable interest. Several functional approaches have shown that surface exposure of pore-lining side chains does not change significantly during activation. However, a disulfide trapping study on ␣1 T6C ␤1 T6C ␥-aminobutyric acid type A (GABA A ) receptors (GABA A Rs), which showed that adjacent ␤ subunits cross-link in the open state only, concluded that channel gating is mediated by ␤ subunits contra-rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…We noted that adjacent ␤ subunits are found only in ␣␤ GABA A Rs, whereas in ␣␤␥ GABA A Rs the ␥ subunit separates the two ␤ subunits . These findings are consistent with previous reports in ␣1␤1 GABA A Rs that adjacent ␤ subunits cross-link via engineered Thr6Ј cysteines in the closed state, whereas nonadjacent ␣ subunits do not cross-link (Shan et al, 2002;Yang et al, 2007). Because of the formation of spontaneous disulfide bonds, we were unable to fully characterize alcohol and MTS reagent modulation of ␣2␤2(T6ЈC) GABA A Rs.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We noted that adjacent ␤ subunits are found only in ␣␤ GABA A Rs, whereas in ␣␤␥ GABA A Rs the ␥ subunit separates the two ␤ subunits . These findings are consistent with previous reports in ␣1␤1 GABA A Rs that adjacent ␤ subunits cross-link via engineered Thr6Ј cysteines in the closed state, whereas nonadjacent ␣ subunits do not cross-link (Shan et al, 2002;Yang et al, 2007). Because of the formation of spontaneous disulfide bonds, we were unable to fully characterize alcohol and MTS reagent modulation of ␣2␤2(T6ЈC) GABA A Rs.…”
Section: Resultssupporting
confidence: 74%
“…Substitution with tryptophan at residue Thr261 (Thr6Ј) in the GABA A R ␣2 subunit enhanced alcohol potentiation (Ueno at el., 2000), suggesting that the tryptophan moiety blocked an alcohol inhibitory site and unmasked additional enhancement by alcohol. Furthermore, cross-linking studies have provided evidence that the 6Ј positions of GABA A R ␣ and ␤ subunits interact (Horenstein et al, 2001;Shan et al, 2002;Yang et al, 2007) and may contribute to a combined inhibitory site for anesthetics (Rosen et al, 2007). In this study, we used site-directed mutagenesis and MTS labeling of GABA A Rs expressed in Xenopus laevis oocytes to test the hypothesis that 6Ј position residues in both ␣2␤2-and ␣2␤2␥2-containing GABA A Rs contribute to the inhibitory effects of alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…It is also unlikely that dimers may have formed between ␤2-K24ЈC and ␣1 or ␥2 subunits due to the lack of nearby free cysteine groups on those subunits. ␤ subunit dimerization has previously been reported to inhibit receptor activation in dimeric ␣1 ␤1-T6ЈC and ␣1 ␤2-E20ЈC GABA A Rs and in trimeric ␣1 ␤1-E20ЈC ␥2 GABA A Rs (39,40,42). These studies concluded that either spontaneous ␤ subunit movements, asymmetric movements of adjacent ␤ subunits, or both were essential for channel activation.…”
Section: Discussionmentioning
confidence: 65%
“…Disulfide trapping has been widely applied to investigate proximity and mobility of engineered Cys-pairs in both soluble and membrane proteins (Falke and Koshland 1987;Matsumura et al 1989;Careaga and Falke 1992b;Pakula and Simon 1992;Zhan et al 1994;Gruber and Capaldi 1996;Danielson et al 1997;Krovetz et al 1997;Yu et al 1999;Elling et al 2000;Horenstein et al 2001Horenstein et al , 2005Shapovalov et al 2003;Bera and Akabas 2005;Chen et al 2006;Yang et al 2007). Here, we use disulfide bond formation as a measure for proximity.…”
Section: Discussionmentioning
confidence: 99%